Microwave line-of-sight path loss prediction on urban street by fuzzy logic model - Supachai Phaiboon (2018)
This paper proposes a method to model the path loss characteristics on urban streets in the microwave band. We applied the concept of fuzzy logic to predict path losses. The input fuzzy sets were classified into five sets, namely 1) Distance between transmitter and receiver, 2) Frequency, 3) Time of day, 4) Transmitting antenna height and 5) Receiving antenna height. These inputs are then inferenced into output path loss via linguistic rules which were trained by measurement. To check the proposed model, we compared the fuzzy prediction with the same and an another measurement. The results show that the fuzzy logic models provided a better prediction. © 2005 IEEE.